Applications of Medical Artificial Intelligence First International Workshop, AMAI 2022, Held in Conjunction with MICCAI 2022, Singapore, September 18, 2022, Proceedings - Wu, Shandong; Shabestari, Behrouz; Xing, Lei. (Cham : Springer Nature Switzerland : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the first International Workshop on Applications of Medical Artificial Intelligence, AMAI 2022, held in conjunction with MICCAI 2022, in Singapore, in September 2022. The book includes 17 papers which were carefully reviewed and selected from 26 full-length submissions. Practical applications of medical AI bring in new challenges and opportunities. The AMAI workshop aims to engage medical AI practitioners and bring more application flavor in clinical, evaluation, human-AI collaboration, new technical strategy, trustfulness, etc., to augment the research and development on the application aspects of medical AI, on top of pure technical research.
Keywords: Computer vision; Application software; Artificial intelligence; Education-Data processing; Social sciences-Data processing; Computer Vision; Computer and Information Systems Applications; Artificial Intelligence; Computers and Education; Computer Application in Social and Behavioral Sciences